Identification of the Mitochondrial ND1 Gene Carrier of Diabetes Mellitus Type 2 with Blood Samples: Identifikasi Gen ND1 Mitokondria Pembawa Sifat Diabetes Mellitus Tipe 2 Melalui Sampel Darah - Amin, Hindah Sabrina; Mushlih, Miftahul (Medicra (Journal of Medical Laboratory Science/Technology), 2020)
Diabetes Mellitus is a condition where there is an increase in blood glucose levels which is characterized by impaired insulin production or the inability of target tissues to respond to insulin. The purpose of this study was to determine the characteristics of the NADH Dehydrogenase 1 gene in the family of Type 2 Diabetes Mellitus patients. The study used a descriptive exploratory method. The sample came from a family of 5 people with T2D in Sidoarjo. Mitochondrial Genotype Analysis using PCR-Primary Sequencing Forward 5'GAGCAGAACCCAACCTCCGAGCAG3 '(nt2826–2849) and Primary Rivers 5'GATTGTTTGGGCTACTGCTCG3' (nt3728 - 3749). Analysis of the 5 samples used obtained 2 samples that can be analyzed with a band length of 690 bp and 84 bp. Based on the results of primary research, the sample used is difficult to get good amplification results. Only one out of five samples can be amplified properly. The variation of the amplified ND1 gene is found at positions T3031C, G3143C, A3252G, C3303T, C3707T.